1993
DOI: 10.1203/00006450-199307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression of Antioxidant Enzymes in the Perinatal Rat Lung

Abstract: ABSTRACT. It has been previously demonstrated that the developing rat lung markedly increases its catalase (CAT) and glutathione peroxidase (GP) activities during the final 10 to 15% of gestation. In the present studies, we tested whether four major antioxidant enzymes (AOE) in perinatal rat lungs might share a similar pattern of developmental AOE gene expression via a pretranslational mechanism. The left lungs of 18-d to term fetuses and early postnatal rat pups were used to measure the concentrations of AOE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…In contrast to our data on immunoreactive SOD [11,12], recent studies showed a wide range of discrepancy between the activity and the m-RNA levels of antioxidant enzymes in fetal rodent organs [4,6]. According to these studies, the expression of antioxidant enzymes appeared to be regulated in a highly variable manner at both the transcriptional and posttranscriptional levels .…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our data on immunoreactive SOD [11,12], recent studies showed a wide range of discrepancy between the activity and the m-RNA levels of antioxidant enzymes in fetal rodent organs [4,6]. According to these studies, the expression of antioxidant enzymes appeared to be regulated in a highly variable manner at both the transcriptional and posttranscriptional levels .…”
contrasting
confidence: 99%
“…Chen et al [4] observed slight perinatal increases in the activities of rat lung CuZnSOD and GSHPx, whereas the m-RNA levels, in contrast, markedly decreased during the same period. Discrepancies between the changes in the levels of m-RNA and proteins were also found in the series of De Haan et al [6].…”
Section: Probability Of Statistically Significant Difference In Immunmentioning
confidence: 97%
“…Such changes have been attributed to early-life exposure to oxygen and cytotoxic reactive oxygen species that injure or reprogram the development of the lungs, eyes, and brain. The lungs of preterm infants are especially at risk for oxidative damage, because antioxidant defenses do not mature until late in gestation (10,11). Consistent with this concept, oxygen supplementation in the neonatal period has been directly associated with altered lung function later in life (12,13).…”
mentioning
confidence: 90%
“…Such changes have been attributed to early-life exposure to oxygen and cytotoxic reactive oxygen species that injure or reprogram the development of the lungs, eyes, and brain. The lungs of preterm infants are especially at risk for oxidative damage, because antioxidant defenses do not mature until late in gestation (10,11). Consistent with this concept, oxygen supplementation in the neonatal period has been directly associated with altered lung function later in life (12,13).…”
mentioning
confidence: 86%